2021
DOI: 10.3390/ijms222111663
|View full text |Cite
|
Sign up to set email alerts
|

Small Intestinal Bacterial Overgrowth as Potential Therapeutic Target in Parkinson’s Disease

Abstract: Increasing evidence suggests that the gut microbiota and the brain are closely connected via the so-called gut–brain axis. Small intestinal bacterial overgrowth (SIBO) is a gut dysbiosis in which the small intestine is abundantly colonized by bacteria that are typically found in the colon. Though not a disease, it may result in intestinal symptoms caused by the accumulation of microbial gases in the intestine. Intestinal inflammation, malabsorption and vitamin imbalances may also develop. SIBO can be eradicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 101 publications
0
25
0
Order By: Relevance
“…6 Accordingly, studies in PD patients have disclosed different patterns, mainly in terms of hydrogenpredominant, methane-predominant, and mixed H2/methane bacterial overgrowth. 6,23 Animal studies have supported this model. Sampson et al reported that colonization of α-synuclein overexpressing mice with microbiota from PD patients magnified motor deficits due to microglial activation and α-synuclein pathology.…”
Section: The Gut-brain Axismentioning
confidence: 99%
See 2 more Smart Citations
“…6 Accordingly, studies in PD patients have disclosed different patterns, mainly in terms of hydrogenpredominant, methane-predominant, and mixed H2/methane bacterial overgrowth. 6,23 Animal studies have supported this model. Sampson et al reported that colonization of α-synuclein overexpressing mice with microbiota from PD patients magnified motor deficits due to microglial activation and α-synuclein pathology.…”
Section: The Gut-brain Axismentioning
confidence: 99%
“…In this review, we aim to critically examine the available evidence regarding the role of Helicobacter pylori and small intestinal bacterial overgrowth (SIBO) in the onset and disease course of patients with PD. Another important role is probably played by GI microbiota-i.e., the complex of bacteria, archaea, fungi, viruses, and parasites that are part of the GI habitat, 6 which is addressed elsewhere.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, H. pylori can cause malabsorption and motor fluctuations independently of SIBO 24 . Recently, it was hypothesized that SIBO might even be implicated in the etiological cascade of PD and that its presence may contribute to the progression of PD through inflammation-induced synucleinopathy 35 . Therefore, the authors of that article consider that eradication of SIBO might be warranted in PD patients even in the absence of GI symptoms.…”
Section: Mechanisms Of Peripheral Levodopa Resistancementioning
confidence: 99%
“…Rifaximin is a broad spectrum antibiotic with poor systemic absorption indicated to treat SIBO [ 210 , 220 , 221 ]. In this respect, rifaximin-mediated SIBO eradication in PD patients resulted in reduced motor fluctuations without impacting on L-dopa treatment [ 222 ].…”
Section: Parkinson’s Disease and Gut Microbiota: Therapeutic Approachesmentioning
confidence: 99%